Interseksionalitas Tokoh Bu Prani Pada Film Budi Pekerti Karya Wregas Bhanuteja: Kajian Feminisme Kimberlé Crenshaw - Aghniya Hanifatil Hakim; Velayati Khairiah Akbar (Journal of Linguistics and Social Studies, 2026)
This study aims to describe the types of intersectionality experienced by the character Bu Prani in the film Budi Pekerti. A qualitative method was employed to describe these intersectional aspects based on Kimberlé Crenshaw’s framework. The data consisted of dialogue, visuals, and scenes from Wregas Bhanuteja’s film Budi Pekerti that illustrate the intersectionality affecting Bu Prani. Data collection involved observation and documentation of the film. The results reveal three types of intersectionality experienced by Bu Prani: (1) structural intersectionality (two instances), (2) representational intersectionality (two instances), and (3) political intersectionality (two instances). These findings indicate that the injustice Bu Prani experiences is shaped not only by gender but also by intersecting factors—such as social constructs, power dynamics in media representation, and school policies—which collectively intensify the forms of adversity she faces.